UPLC-MS/MS method for simultaneous determination of pyrantel, praziquantel, febantel, fenbendazole and oxfendazole in dog plasma and its application to a bioequivalence study - Zhang, Fengyichi; Guo, Fanxi; Zhao, Xinyu; Li, Chongyang; Wang, Junli; Wang, Mengyun; Ma, Ruixia; Chen, Baochang; Miao, Qiangqiang; Wang, Yimeng; Wang, Zihan; Cao, Di; et al. (Frontiers in Pharmacology, 2025)
A rapid, sensitive and reliable ultra–performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) was developed and validated for the simultaneous quantitation of pyrantel (PYR), praziquantel (PRA), febantel (FBT) and its active metabolites, fenbendazole (FEN) and oxfendazole (OXF) in dog plasma. Fenbendazole–D3 (FEN–D3) was used as an internal standard (IS). The analytes and IS were prepared using simple protein precipitation (PP) combined with liquid–liquid extraction (LLE). Chromatographic analysis was performed on UPLC BEH C18 column using acetonitrile–0.1% formic acid in water for gradient elution. Detection was carried out in multiple reaction monitoring (MRM) mode under positive electrospray ionization. The standard curves were linear through the concentration range of 4–240 ng/mL for PYR and OXF, 15–900 ng/mL for PRA, 2–120 ng/mL for FBT and 10–600 ng/mL for FEN with all correlation coefficients >0.99. The intra–and inter–batch precision was 1.08%–14.26% and accuracy was from 90.66% to 110.28%. The mean extraction recoveries for the analytes and IS were >90%. The total run time was 9.0 min. The developed method was successfully applied to a bioequivalence study after oral administration of compound febantel tablets in 38 healthy dogs.